DIGITAL BASED EDUCATION: SMART MOM BREASTFEEDING - Ratna Ningsih; Annisa Riska Hidayani; Maliha Amin; Imelda Erman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
Post partum period mothers, especially primipara, often experience problems in the breastfeeding process, this is due to a lack of mother's knowledge, including the lack of information obtained by mothers from health workers and the mother's lack of ability to understand the information obtained, and also do not have experience giving birth. The objectives of this study was to increase the knowledge and ability of mothers in breastfeeding and the baby's ability to breastfeed so that breastfeeding was smooth. This type of research is descriptive in the form of a case study. The subjects studied were 2 patients with the same nursing cases and problems, namely patients with primiparous mothers with ineffective breastfeeding at Muhammadiyah Hospital Palembang. This research was conducted on March 9, 2022 to March 11 2022 and April 12 to April 14 2022. After implementing digital-based education on the audiovisual method for smart breastfeeding mothers, digital-based education results showed that smart mother breastfeeding can increase mothers’ knowledge and ability to breastfeeding as well as babies’ ability to suckle and breastfeeding smoothly. Implementation of digital-based education: smart mother breastfeeding can be applied.